2001
DOI: 10.1515/jpm.2001.042
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of fatty acids in plasma and erythrocyte phospholipids during pregnancy

Abstract: There was a significant decrease in the proportion of omega 3 PUFA in plasma from the first to the third trimester. Thus, it is suggested that the omega 3 PUFA intake during pregnancy should be increased in the last trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
2
18
1
Order By: Relevance
“…Maternal plasma DHA content commonly declines during pregnancy (Al et al, 1995a;Otto et al, 1997;Matorras et al, 2001), particularly in later pregnancy (Knopp, 1991) when foetal requirements for LCPUFA are highest (Clandinin, 1999;Al et al, 2000). In the current study, this pattern was not observed in the control group, possibly because the initial maternal stores were higher than reported in other populations (Matorras et al, 2001).…”
Section: Discussioncontrasting
confidence: 65%
“…Maternal plasma DHA content commonly declines during pregnancy (Al et al, 1995a;Otto et al, 1997;Matorras et al, 2001), particularly in later pregnancy (Knopp, 1991) when foetal requirements for LCPUFA are highest (Clandinin, 1999;Al et al, 2000). In the current study, this pattern was not observed in the control group, possibly because the initial maternal stores were higher than reported in other populations (Matorras et al, 2001).…”
Section: Discussioncontrasting
confidence: 65%
“…Table 3 shows that all the parameters were insignificantly higher in the first trimester. Findings of the other studies [37,38] are similar to our findings. In pregnancy, serum total cholesterol and HDL-cholesterol levels show increases parallel with the months of pregnancy, especially during late pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…During pregnancy, there is a faster turnover of PUFA from fast storage that may modify the profile of erythrocyte cell membrane fatty acids [15]. A significant decrease in the proportion of n-3 PUFA from the first to the third trimester has been noted [21]. Thus, it is suggested that n-3 PUFA intake during pregnancy should be increased in the last trimester.…”
Section: Smoking Hormonal Contraception Pregnancy and Premenstrual mentioning
confidence: 99%